Metabolic regulation in mitochondria as a prospective way of body rejuvenation - E.G. Manzhalii; V.V. Dunaevskaya; O.M. Baka (Publishing House TRILIST, 2021)
Scientists around the world are looking for ways to achieve high-quality and active longevity. The complexity of these searches is associated with the lack of unified concept of aging mechanisms, the problem of extrapolating the results of studies of geroprotectors from model organisms to humans. Therefore, modern medicine can only slow down the aging process so far. Nevertheless, it has been proven that disturbances in the functioning of mitochondria are an important link in the pathogenesis of aging; therefore, regulation of their metabolism is a promising way of rejuvenating the body. A decrease in protein synthesis and a general decrease in the intensity of the oxidative enzymes action are interrelated. Energy production for the protein and DNA synthesis decreases with a decrease in the intensity of oxidative processes. Dysfunction of mitochondrial adaptive reactions also develops with age, which may be associated with the low efficiency of the NADH dehydrogenase complex - NADH ubiquinone oxidoreductase, which catalyzes the transfer of electrons from NADH to ubiquinone/coenzyme Q10, resulting in a decrease in electron transport and an increase of active oxygen forms. Coenzyme Q10 reducing plays a very important role in the aging process, as it is an antioxidant and, unlike other antioxidants, is produced in the body. An increase in mitochondrial biogenesis, as well as an increase in the rate and efficiency of mitochondrial metabolism (with a calorie restricted diet for example) helps to improve the energy supply of cells and prolong life. A drug based on xylitol Xylate can be a source of triglycerophosphate by metabolism through the pentose phosphate cycle and thereby reduce the amount of free fatty acids that can be oxidized into acetyl-CoA, increases the content of adenosine triphosphate acid and other adenine nucleotides in liver, and has a pronounced antiketogenic effect. It can reduce intoxication and improve microcirculation, which is especially important for high-quality and active longevity. Activation of mitochondrial metabolism is a promising direction in the aging prevention, since it allows balancing metabolic processes not only in cells, but also in body as a whole.